Morphological characteristics and biological cycle of the hoverfly Eristalinus arvorum (Fabricius, 1787) (Diptera, Syrphidae) - Cao, Liang; Zeng, Qing; Ren, Qiuxia; Zeng, Aiping; Zhang, Yongsheng (Frontiers in Sustainable Food Systems, 2022)
The hoverfly Eristalinus arvorum (Fabricius, 1787) (Diptera: Syrphidae), which belongs to the tribe Eristalini, is well known as a pollinating agent for crops and flowering plants in agricultural and natural ecosystems. Large quantity, wide distribution and their ecological function of the hoverfly E. arvorum make them an appropriate candidate for use as pollinators and environmental indicator species. However, little information has been known on the morphology and the biological cycle of the hoverfly. In this study, feeding experiments under artificial climate chamber and morphological qualitative and quantitative observations were carried out to study the morphology and the biological cycle of the hoverfly E. arvorum. The morphology of eggs, larvae, pupae, and adults of E. arvorum were described in detail for the first time. A complete generation of E. arvorum lasts about 30.12 ± 0.14 days, and there is no significant difference in body length between males (10.27 ± 0.29 mm) and females (11.16 ± 0.45 mm). The most noteworthy morphological features of E. arvorum are the stripes on the compound eyes, the mesonotum, and the abdomen of adults, the chorionic structure consisting of fusiform units on the egg's surface, and the anterior spiracles and pupal spiracles of the pupae. Thus, the detailed description based on morphology and life history will provide the basis for the identification, biodiversity conservation and artificial breeding of the hoverfly E. arvorum.